Cotton descriptors (Revised) - International Board for Plant Genetic Resources (International Board for Plant Genetic Resources, 1985)
This descriptor list, which has been prepared according to a standard IBPGR format, supersedes the list published in 1980. Descriptors are grouped under the following headings: (1) accession data, dealing with identification; (2) collection data, including details recorded by collectors; (3) date relating to site at which preliminary evaluation is carried out; (4) plant data, including vegetative, inflorescence and fruit traits; (5) and (6) similar data recorded during further evaluation; (7) stress susceptibility; (8) pest and disease susceptibility; (9) alloenzyme composition; (10) cytological characters and identified genes; and (11) notes. The information in categories (1) to (4) is considered the minimum that should be available for any one accession. A list of Gossypium species, including tetraploids, and their genome designations are given in an appendix.